2008
DOI: 10.3892/ijmm.22.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic analysis of aged skeletal muscle

Abstract: Abstract. One of the most important post-translational modifications is represented by phosphorylation on tyrosine, threonine and serine residues. Since abnormal phosphorylation is associated with various pathologies, it was of interest to perform a phosphoproteomic profiling of age-related skeletal muscle degeneration. We used the fluorescent phosphospecific Pro-Q Diamond dye to determine whether changes in the overall phosphorylation of the soluble skeletal muscle proteome differs significantly between young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 59 publications
3
70
0
1
Order By: Relevance
“…Finally, an age-related increase in susceptibility to damage could be due to environmental factors. Elevations in reactive oxygen species (Fielding and Meydani 1997) and altered protein phosphorylation (Gannon et al 2008) are hallmarks of aging muscle. Acute oxidative stress exacerbates eccentric contraction-induced injury in old laboratory animals (Zerba et al 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, an age-related increase in susceptibility to damage could be due to environmental factors. Elevations in reactive oxygen species (Fielding and Meydani 1997) and altered protein phosphorylation (Gannon et al 2008) are hallmarks of aging muscle. Acute oxidative stress exacerbates eccentric contraction-induced injury in old laboratory animals (Zerba et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Acute oxidative stress exacerbates eccentric contraction-induced injury in old laboratory animals (Zerba et al 1990). Myosin light chain 2 shows an age-related increase in phosphorylation (Gannon et al 2008), an alteration that has been shown to increase susceptibility to contraction-induced damage in fast fibers from adult rodents (Childers and McDonald 2004). Desmin and tropomyosin, two other strain sensitive proteins, also show increased phosphorylation with aging (Gannon et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Pyruvate isoform PK-M1 exists as 5 sub-species with differing isoelectric points in skeletal muscle tissues, whereby theses isozymes display varying degrees of phosphorylation and glycosylation [21,24]. Previous studies have clearly shown that the PK isoform exhibiting a pI of 6.6 and an apparent molecular mass of 57.8 kDa is several-fold decreased in senescent muscle fibres [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, comparative subproteomics of the soluble myofibril-enriched fraction has shown distinct age-dependent effects on the contractile apparatus. The contractile protein exhibiting the most drastically changed expression was identified as the MLC2 isoform of the slowtype myosin light chain [23], which also exhibits enhanced phosphorylation levels in aged fibres [24]. Although fast and slow isoforms of myosin heavy chain switch in the majority of aged fibres, the dramatic increase in slow MLC2 expression was restricted to individual senescent cells [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation